The Indirect Effects of Oil Price on Consumption Through Assets - Razmi, Seyedeh Fatemeh; Torki, Leila; Razmi, Seyed Mohammad Javad; Mohaghegh Dowlatabadi, Ehsan (International Journal of Energy Economics and Policy, 2022)
This research considers how oil price can indirectly affect consumption through asset prices of stock and house. Using the theory of consumption wealth effect, this research shows that, unexpectedly, a rise in oil price would lead to increase in consumption. The research uses the data of three OECD countries of France, Canada and the United States from quarter 1st 1997 to quarter 3rd 2017 and vector autoregression model. Empirical results prove that a positive shock to oil price has a positive indirect effect on consumptions of France and Canada via both asset prices. The indirect effect of oil price on US consumption only exists through stock price. The duration of indirect effect of oil price on consumption depends on dependency of consumption to asset prices in each country.